NFC technology acceptance for mobile payments: A Brazilian Perspective - de Luna, Iviane Ramos; Montoro-Ríos, Francisco; Liébana-Cabanillas, Francisco; de Luna, João Gil (Review of Business Management, 2017)
Purpose – This study investigates the acceptance of NFC technology for payment through mobile in a Brazilian context, which allow knowing the factors that influence directly or indirectly in that acceptance. Design/methodology/approach – Through an online and selfadministered questionnaire and using the snowball sampling procedure on social networks, the final sample consisted of 423 mobile phone users in Brazil and the technique used to prove the hypotheses was the Structural Equation Model. Findings – The results show that attitude, personal innovation in IT and perceived usefulness are determinants of future intention to use the NFC technology for payments in Brazil. Originality/value – The proposed model has a predictive power of intention to use NFC payment of 71%, demonstrating that it includes background with a large predictive power of acceptance of NFC technology which led us to highlight the main implications for the management and development of new studies in this field.